Predator-prey System with the Effect of Environmental Fluctuation - Lan, Le Hong (VNU Journal of Science: Mathematics - Physics; Vol 30 No 3, 2014)
Abstract: In this paper we study the trajectory behavior of Lotka - Volterra predator - prey systems with periodic coefficients under telegraph noises. We describe the  - limit set of the solution, give sufficient conditions for the persistence and prove the existence of a Markov periodic solution. Keywords: Key words and phrases, Lotka-Volterra Equation, Predator - Prey, Telegraph noise,  - limit set, Markov periodic solution.